Hubungan Kemandirian Belajar Dengan Kemampuan Pemahaman Konsep Matematika Di Kelas V - Uray Cempaka Regina; Toriana Toriana; Rien Anitra; Rini Setyowati (UNIKU PRESS, 2021)
The purpose of this study is to see the student's learning self-reliance relationship with the students' ability to understand mathematical concepts. The type of this research is correlation study with quantitative approach. Research population is the fifth grade student of SDN 7 singkawang. The sampling technique in this study is a tedium sampling technique. The sample in this study is all of the fifth grade student in SDN 7 singkawang consist of student in Class V a and Vb . Total of student are 47 students. The data-gathering techniques in this study are based on questionaire techniques and measurement techniques, which involve using students' learning self-reliance questionaire and test students' mathematical concepts abilities in space materials. The technique of data analyzing is the spearman rank correlation. Research shows that, 1) a student's learning level of self-reliance is improved on the basis of a student's rate percentage percentage with an average of 63.4. 2) the level of ability to understand the concept of mathematicians is inproved with a high average of 14.6. 3) there is a corelation between student learning self-reliance and students' 3.02 student mathematical ability, with a 0.41 correlation value and a compound coefficiencies of 1681%. So based on the research that has been done there is a corelation between learning self-reliance and the ability to understand student mathematics concepts. Keywords : self-reliance learn, the ability to understand concepts, build space